Pengaruh Pendidikan Kewirausahaan, Sikap Kewirausahaan, dan Motivasi Terhadap Minat Berwirausaha Peserta Didik - Almadhea, Daphne Rizka; Ulfa Kamalia, Putri (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
data from the Coordinating Ministry for Human Development and Culture, only 1.9 million high school graduates continued their education to tertiary institutions, the rest entered the increasingly tight world of work. This is in accordance with BPS data which reveals that around 9% of open unemployment is dominated by high school graduates. This research aims to analyze the influence of entrepreneurship education, entrepreneurial attitudes, and motivation on students' entrepreneurial interest. This research is a type of quantitative associative research with a research sample of 113 students from Senior High School of Hang Tuah 4 Surabaya who were analyzed using multiple linear regression analysis techniques. The results of the research state that entrepreneurship education influences on the entrepreneurship interest, entrepreneurial attitude influences on the entrepreneurship interest, motivation influences on the entrepreneurship interest, and entrepreneurship education, entrepreneurial attitude and motivation simultaneously influence on the entrepreneurship interest.